2016
DOI: 10.3389/fphar.2016.00474
|View full text |Cite
|
Sign up to set email alerts
|

Golden Needle Mushroom: A Culinary Medicine with Evidenced-Based Biological Activities and Health Promoting Properties

Abstract: Flammulina velutipes (enoki, velvet shank, golden needle mushroom or winter mushroom), one of the main edible mushrooms on the market, has long been recognized for its nutritional value and delicious taste. In recent decades, research has expanded beyond detailing its nutritional composition and delved into the biological activities and potential health benefits of its constituents. Many bioactive constituents from a range of families have been isolated from different parts of the mushroom, including carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
113
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 173 publications
(325 reference statements)
0
113
1
6
Order By: Relevance
“…Nutritionally, mushrooms provide key nutrients, amino acids, monosaccharides, dietary fiber, and many bioactive components. Recent reports indicated that edible mushroom extracts exhibit promising therapeutic and health-promoting benefits, particularly in relation to diseases associated with inflammation (Muszyńska, Grzywacz-Kisielewska, Kała, & Gdula-Argasińska, 2018), anticancer activities, anti-atherosclerotic, antihypertensive, and cholesterol lowering effects, anti-aging and antioxidant properties (Ren, Perera, & Hemar, 2012;Schneider et al, 2011;Tang et al, 2016). With respect to organoleptic properties, Tsai, Tsai, and Mau (2008) reported that the taste of a mushroom extract was primarily attributed to free amino acids, nucleotides, and soluble sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritionally, mushrooms provide key nutrients, amino acids, monosaccharides, dietary fiber, and many bioactive components. Recent reports indicated that edible mushroom extracts exhibit promising therapeutic and health-promoting benefits, particularly in relation to diseases associated with inflammation (Muszyńska, Grzywacz-Kisielewska, Kała, & Gdula-Argasińska, 2018), anticancer activities, anti-atherosclerotic, antihypertensive, and cholesterol lowering effects, anti-aging and antioxidant properties (Ren, Perera, & Hemar, 2012;Schneider et al, 2011;Tang et al, 2016). With respect to organoleptic properties, Tsai, Tsai, and Mau (2008) reported that the taste of a mushroom extract was primarily attributed to free amino acids, nucleotides, and soluble sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivated edible mushrooms are good sources of protein, have low-fat content, and are cholesterol free [2]. Mushrooms are also very popular as a quality protein containing essential amino acids, adequate vitamins, minerals, and are rich source of different unsaturated fatty acids [3]. Different bioactive components have been extracted from the fruiting body and mycelium part of mushroom and tested in invitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Different bioactive components have been extracted from the fruiting body and mycelium part of mushroom and tested in invitro studies. Polysaccharides are considered to be the most activate component in mushrooms which have immune stimulating activities [3]. In addition, the polysaccharides in mushroom have been found to produce different cytokines and increase the weight of immune stimulating organs in laboratory animals [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, plants have been used to treat various diseases in many developing countries and become the basis of many traditional medicine systems to provide mankind with new remedies (Fabricant and Farnsworth, 2001; Tan et al, 2016a,b; Tang et al, 2016). Since ancient time, phytochemicals have been used to treat inflammation (Tan et al, 2015; Chan et al, 2016; Yong et al, 2016), beginning with the discovery of aspirin as the first anti-inflammatory and analgesic drug (Vane and Botting, 1987).…”
Section: Introductionmentioning
confidence: 99%